Penerapan Permainan Tradisional (Congklak) dalam Meningkatkan Kemampuan Kognitifanak Usia 5-6 Tahun di TK Al-Ikhlas TembungKecamatan Percut Sei Tuan - Lutfiah Aini; Khadijah Khadijah; Zulkipli Nasution (Institut Nalanda, 2024)
This research aims to determine: 1) the cognitive abilities of children aged 5-6 years before implementing traditional games (congklak) in Al-Ikhlas Tembung Kindergarten, Percut Sei District. 2) to determine the cognitive abilities of children aged 5-6 years through traditional games (congklak) at Al-Ikhlas Tembung Kindergarten, Percut Sei District. This type of research is in the form of Classroom Action Research (PTK). The research subjects were conducted at Al-Ikhlas Tembung Kindergarten, Percut Sei Tuan District, totaling 12 children. Increasing children's cognitive abilities in cycle I, namely by using traditional game media (congklak), there were 2 children (17%) with very good development criteria. In this cycle, the increase in children's cognitive abilities is considered to have not yet reached the indicators of success. In cycle II there was a significant increase in cognitive abilities, of the 12 children there were 10 children (83%) with the criteria for developing very well. In this cycle, children's cognitive abilities have been reached, namely 75%. Thus, it can be concluded that the cognitive abilities of children aged 5-6 years through traditional games (congklak) in Al-Ikhlas Tembung Kindergarten, Percut Sei Tuan District in cycle I to cycle II were obtained.